Penerapan Prinsip Desain Antarmuka dalam Evaluasi User Interface dan User Experience E-Learning - Fathurrahman, Muhammad Ikhsan; Sumarsono, Sumarsono (Jurnal Komtika (Komputasi dan Informatika), 2024)
Application of Interface Design Principles in Evaluation of E-Learning User Interface and User Experience The aspects of user interface and user experience play an important role in determining the success of an e-learning platform. An intuitive user interface and positive user experience can increase user participation and satisfaction, and facilitate the learning process. However, based on interviews with developers, there has never been an evaluation of UIN Sunan Kalijaga's e-learning in terms of user interface and user experience. This raises the need to evaluate the extent to which the e-learning meets good interface design standards to improve user effectiveness and comfort. This research uses descriptive method because this research is explaining or describing the phenomenon under study. The approach used in this research is a quantitative approach. Data was obtained from a closed questionnaire consisting of 15 statements using a Likert scale with 4 dimensions of assessment. This study concluded that the level of user comfort in using UIN Sunan Kalijaga e-learning is in the good enough category with a value of 69.57%. This analysis revealed that the consistency aspect received the highest score, while the appearance and security and prevent errors aspects received the lowest score.